Landmark learning by the Ozark zigzag salamander Plethodon angusticlavius - Adam L. CRANE, Alicia MATHIS (Current Zoology, 2011)
Although salamanders have been shown to respond to classical conditioning, spatial learning has been largely unstudied. We tested whether salamanders could learn to locate foraging areas by using landmarks. We trained 10 salamanders Plethodon angusticlavius to use landmarks (small rocks) to locate patches within the arena containing food (blackworms Lumbriculus variegatus). At the corners of each square testing arena were four plastic dishes, one containing blackworms and the other three empty. A rock was placed in front of the dish containing blackworms, and the location of the food-dish was randomly chosen for each training trial. A control group was also trained to feed on blackworms in the presence of a rock, but the rock was positioned randomly among the four dish locations so that the rock was not a reliable landmark for the worms. Although the length of the training period for individual salamanders varied (22–38 trainings per individual), the mean number of trainings for salamanders in the control and experimental groups was equal (30 training trials). During testing, no blackworms were present to eliminate any visual or chemical cues emanating directly from the prey. Individuals trained with the rock landmarks spent significantly more time in the area of the landmark than did control salamanders [Current Zoology 57 (4): 485–490, 2011].